Valuation of timber and firewood of trees outside forest along the urban–rural gradient in Kathmandu valley, Nepal - Shrestha, Babita; Sharma, Bhuvan Keshar; Yadav, Ram Kailash Prasad (Banko Janakari, 2022)
This study aims to analyze diameter class, quality class, wood production potential and timber and firewood values of trees outside forest along the urban-rural gradient in Kathmandu valley of central Nepal. Inventory was performed in 209 randomly selected points. Circular plots of 20 m radius were used for inventory. All trees (height > 1.3 m and DBH ≥ 5 cm) in the plots were identified to species level and their height, DBH & quality class were recorded. In total 6,210 trees (236.35 ha-1) of 150 species belonging to 111 genera and 57 families were recorded. The total merchantable timber volumes of timber class A and B, and total timber volumes were highest in the urban stratum (537.08, 84.88 and 621.96 cu ft ha -1 respectively) followed by rural (442.94, 66.82 and 509.76 cu ft ha -1 respectively) and suburban (250.04, 47.31 and 297.35 cu ft ha -1 respectively) strata. But due to higher merchantable price of tree species recorded in rural stratum, total market value of class A timber was higher in rural stratum (NPR 7,89,871/US$ 6,085), class B timber was higher in urban stratum (NPR 1,08,255/US$ 834), total timber was higher in rural stratum (NPR 8,70,410/US$ 6,706), firewood was higher in urban stratum (NPR 4,88,709/US$ 3,765) and total wood was higher in urban stratum (NPR 12,95,531/US$ 9,981). Cinnamomum camphora was found as tree species with highest market price of total wood value in the study area. The study provides the baseline data of useful timber species through TOF suggesting a need for appropriate timber producing species selection for plantation.